Heat-resistant low-carbon concrete and preparation method thereof

By using tuff powder and corn cob ash to prepare porous refractory aggregates, combined with heat shrinkable basalt fibers, the problem of heat-resistant concrete prone to cracking at high temperatures is solved, and the goals of high temperature crack resistance and low carbon environmental protection are achieved.

CN117361956BActive Publication Date: 2025-04-29JIANGSU CHINA CONSTR COMMERCIAL CONCRETE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311400277.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

Existing heat-resistant concrete is prone to cracking at high temperatures, and natural refractory aggregate resources are short of resources, making it difficult to meet the requirements of high temperature crack resistance and low carbon environmental protection.

Method used

Refractory aggregates are prepared by tuff powder and corn cob ash, and combined with heat-shrinkable basalt fibers, porous aggregates are prepared through freeze-drying technology to improve the heat resistance and crack resistance of concrete.

Benefits of technology

It effectively improves the crack resistance of concrete at high temperatures, reduces the quality of aggregates, achieves the goal of low carbon and environmental protection, and solves the problem of shortage of natural refractory aggregate resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004515036250000091
    Figure BDA0004515036250000091
Patent Text Reader

Abstract

The invention discloses a heat-resistant low-carbon concrete and a preparation method thereof, belonging to the technical field of concrete. The concrete comprises the following components in parts by weight: 300-350 parts of cement, 110-150 parts of composite admixture, 1000-1400 parts of refractory aggregate, 650-850 parts of granite powder sand, 50-60 parts of heat-shrinkable basalt fiber, 3.5-8.0 parts of water reducer, and 142-165 parts of water; the preparation method of the refractory aggregate comprises the following steps: S1. Evenly mix tuff powder and NaOH solution; S2. Add corn cob ash, silicate cement and modified tuff powder into a granulator, stir evenly, spray water for granulation, and obtain aggregate after screening; S3. Freeze the obtained aggregate at -10-5°C, and obtain refractory aggregate after low-temperature vacuum drying. The present invention obtains a refractory aggregate with a closed outer surface and porous inner part under the synergistic effect of tuff powder, corncob ash and freeze drying, and the heat shrinkable fiber is used in combination to improve the heat resistance and crack resistance of concrete at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to a heat-resistant low-carbon concrete and a preparation method thereof. Background Art

[0002] With the rapid development of my country's economy, concrete technology is also developing in a diversified direction. For some special projects such as ocean, nuclear power plants, geothermal projects, solar thermal power plants, etc., ordinary concrete can no longer meet the requirements, and it is necessary to develop a concrete with excellent heat resistance.

[0003] Heat-resistant concrete is a special concrete that can be used for a long time at 200℃~900℃ and can maintain the required physical and mechanical properties and volume stability. Generally, heat-resistant concrete is made of heat-resistant cementitious materials, heat-resistant coarse and fine aggregates and water in a certain proportion. The amount of aggregate generally accounts for about 75% of the total mass of concrete, which is also the main factor affecting the heat resistance of concrete. When using aggregates with a small thermal expansion coefficient, it is not only beneficial to improve the heat resistance of concrete, but also to improve the density of concrete. Traditional refractory aggregates include igneous rocks, crushed clay bricks, clay, clinker, crushed magnesium bricks and magnesia sand. Practice has proved that it is safe to use basalt, andesite, diabase, granite silt sand and other igneous rocks as aggregates to prepare heat-resistant concrete with a use temperature below 500℃, but when the temperature exceeds 700℃, the concrete will crack greatly, posing a safety hazard. For example, Chinese patent CN111908870A discloses a heat-resistant refractory concrete and a preparation method thereof. The heat-resistant refractory concrete comprises the following components by weight: 1000-1100 parts of refractory coarse aggregate, 600-700 parts of refractory fine aggregate, 300-400 parts of ordinary Portland cement, 60-120 parts of mineral powder, 30-60 parts of high alumina powder, 7-13 parts of silicon powder, 8-12 parts of polycarboxylic acid water reducer, 1-5 parts of dispersant, and 150-200 parts of water; the refractory coarse aggregate comprises at least one of granite silt sand, diabase, andesite, basalt, syenite, and diorite; the refractory fine aggregate is a mixture of refractory andesite and basalt with a particle size of 0.15-5 mm. The invention provides a good heat-resistant and fire-proof foundation for concrete by selecting refractory coarse aggregate and refractory fine aggregate, and uses high-aluminum powder, silica powder and other powders with excellent heat-resistant and fire-proof properties, and is supplemented with additives such as polycarboxylic acid water reducer and dispersant, so that concrete can have good heat-resistant and fire-proof properties and construction performance. However, the invention uses igneous rock as refractory aggregate, which cannot improve the crack resistance of concrete at high temperatures. When the concrete is subjected to a high temperature of 700°C, it is easy to crack significantly.

[0004] On the other hand, in recent years, with the increasing scarcity of natural resources and the increasingly severe environmental protection situation, there are fewer and fewer natural refractory aggregates that meet the requirements; therefore, it is of great practical significance to provide a refractory aggregate prepared from solid waste to prepare heat-resistant concrete with better performance. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, one of the purposes of the present invention is to provide a heat-resistant low-carbon concrete, which adopts refractory aggregate prepared from solid waste and is used in combination with heat-shrinkable basalt fiber, so that the concrete has excellent heat resistance and crack resistance at high temperatures, thereby solving the problem of easy cracking of concrete after high temperature in the prior art. At the same time, solid waste is effectively utilized to develop eco-friendly low-carbon heat-resistant concrete, thereby solving the problem of shortage of natural refractory aggregate resources in the prior art.

[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0007] A heat-resistant low-carbon concrete comprises the following components in parts by weight: 300-350 parts of cement, 110-150 parts of composite admixture, 1000-1400 parts of refractory aggregate, 650-850 parts of granite powder sand, 50-60 parts of heat-shrinkable basalt fiber, 3.5-8.0 parts of water reducer, and 142-165 parts of water;

[0008] The preparation method of the refractory aggregate comprises the following steps:

[0009] S1. The tuff powder and the NaOH solution are mixed evenly, and the modified tuff powder is obtained after drying;

[0010] S2. Add corncob ash, silicate cement and modified tuff powder into a granulator, stir evenly, spray water for granulation, and obtain aggregate with a particle size of 5 to 10 mm after sieving;

[0011] S3. The obtained aggregate is frozen at -10 to -5°C, and then low-temperature vacuum dried to obtain the refractory aggregate.

[0012] The present invention uses tuff powder and corncob ash to prepare refractory aggregate, which can effectively utilize solid waste and achieve a low-carbon effect. Tuff powder is used as a precursor, and sodium hydroxide is used to stimulate the activity of tuff powder, so that quartz, albite, potassium feldspar, calcium feldspar, micro-grained feldspar and sodalite in the tuff are dissolved in an alkaline environment to produce active aluminosilicate monomers. The active aluminosilicate reacts with Ca 2+The reaction generates cementitious products such as hydrated calcium silicate and hydrated aluminum silicate, which can significantly improve the strength of aggregates; corn cob ash has a volcanic ash effect, which can not only reduce the amount of cement, but also realize the reuse of biomass ash. More importantly, the water absorption rate of tuff powder is high, and corn cob ash has the effect of delaying the setting time of cement. Adding corn cob ash can delay the time of aggregate forming, setting and hardening in step S2, so that tuff has sufficient time to absorb water and saturate during the granulation process. Then step S3 turns the water into solid ice at low temperature, and then uses low-temperature vacuum drying to directly sublimate the ice into water vapor, so as to obtain an aggregate with a closed outer surface and a porous inner surface; compared with dense aggregate, the thermal insulation of porous aggregate is enhanced, and the mass of aggregate can be reduced by 30-40%, which is conducive to the lightweight of concrete structure.

[0013] The heat-shrinkable basalt fiber of the present invention will shrink when heated. When the heat-shrinkable basalt fiber is added to concrete, when the temperature inside the concrete rises to 600°C, the heat-shrinkable basalt fiber inside the concrete will shrink and deform, so that a tensile stress is generated inside the concrete to resist the phenomenon of concrete expansion due to heat, maintain the thermal stability of the concrete volume, improve the crack resistance of the concrete at high temperature, and solve the problem that the concrete is prone to expansion after being heated, resulting in concrete cracking.

[0014] Preferably, in step S1, the mass ratio of the tuff powder to the NaOH solution is (0.6-1.2):(6-10), and the mass concentration of the NaOH solution is 6%-12%.

[0015] Preferably, in step S2, the mass ratio of the corncob ash, silicate cement, modified tuff powder and water is (0.6-1.5):(2-6):(0.5-2.0):(0.7-2.5).

[0016] Preferably, the corncob ash is obtained by calcining corncobs at 815-850° C. for 1.5-3 hours.

[0017] Preferably, the low-temperature vacuum drying conditions are sublimation drying at a temperature of -60 to -40°C and a vacuum of 10 to 30 Pa for 20 to 24 hours.

[0018] Preferably, the method for preparing the heat-shrinkable basalt fiber comprises the following steps:

[0019] P1. The basalt fiber and spodumene are mixed and ground, kept at 150-250°C for 10-14h, then heated to 350-450°C for 10-14h, then heated to 550-650°C for 0.5-1.5h, and then cooled to obtain a mixed powder;

[0020] P2. The obtained mixed powder is evenly mixed with high-rubber powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2, and heat-shrinkable basalt fiber is obtained after melt extrusion, spinning and cutting.

[0021] The present invention mixes basalt fiber and spodumene and calcines them to make heat-shrinkable fiber. Spodumene (LiAlSi2O4) glass-ceramics is mainly divided into three variants: α-spodumene, β-spodumene and γ-spodumene; wherein α-spodumene is a stable variant at low temperature, β-spodumene is a high-temperature stable variant, and its thermal expansion coefficient is extremely low. When the temperature exceeds 600°C, α-spodumene undergoes a phase transition, precipitates β-spodumene and combines with SiO2 in the basalt fiber to generate a β-spodumene solid solution with higher thermal stability. As the proportion of the β-spodumene solid solution continues to increase, the thermal expansion coefficient of the material tends to a negative value, so that the basalt fiber has the characteristic of high-temperature shrinkage.

[0022] The present invention adds basalt fiber as a reinforcement into a spodumene glass-ceramic matrix, composites it with the spodumene glass-ceramic matrix to form a reinforced composite material similar to a polymer blend, and then manufactures heat-shrinkable basalt fiber through processes such as melting and extrusion.

[0023] Preferably, in step P1, the mass ratio of the basalt fiber to spodumene is (2-7):(4-10).

[0024] Preferably, in step P2, the mass ratio of the mixed powder to high-glue powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2 is (8-15): (10-20): (8-15): (5-10): (2-5): (0.5-2.0).

[0025] Preferably, the compatibilizer is obtained by copolymerization of styrene and maleic anhydride.

[0026] Preferably, the composite admixture comprises silica fume and fly ash in a mass ratio of 1:(1-2).

[0027] Another object of the present invention is to provide a method for preparing the heat-resistant low-carbon concrete, comprising the following steps:

[0028] M1. Weigh each component by weight;

[0029] M2. The cement and composite admixture are mixed evenly, and then the granite silt sand, water reducer and water are added. After mixing evenly, the refractory aggregate is added. After mixing evenly, the heat-shrinkable basalt fiber is added. After mixing, pouring, curing and demolding, heat-resistant low-carbon concrete is obtained.

[0030] Among them, the water demand of refractory aggregate increases. Before use, the refractory aggregate is soaked in water for 12 to 24 hours to obtain saturated surface-dry refractory aggregate, which is beneficial to control the water-cement ratio of concrete and ensure the molding state of concrete.

[0031] Compared with the prior art, the present invention is beneficial in that:

[0032] (1) The present invention obtains a refractory aggregate with a closed outer surface and porous inner part under the synergistic effect of tuff powder, corn cob ash and freeze drying. On the one hand, it realizes the effective utilization of solid waste resources and solves the problem of shortage of natural refractory aggregate resources; on the other hand, the aggregate with a closed outer surface and porous inner part can improve the heat resistance of concrete. At the same time, the aggregate has a porous structure, and the thermal expansion coefficient and thermal conductivity are low after heating, which can reduce the expansion deformation of concrete in a high temperature environment, and cooperate with the heat shrinkable fiber to improve the crack resistance of concrete at high temperature.

[0033] (2) The present invention successfully prepares heat-shrinkable basalt fiber from basalt fiber and spodumene, and adds the heat-shrinkable basalt fiber to concrete. Under high temperature, the concrete will shrink and deform, so that a tensile stress is generated inside the concrete to resist the thermal expansion of the concrete, maintain the thermal stability of the concrete volume, and improve the crack resistance of the concrete under high temperature.

[0034] (3) Compared with the preparation of artificial aggregate by high-temperature calcination, the present invention adopts condensation pelletizing technology to realize the preparation technology of artificial aggregate without calcination, reduces energy consumption, and has broad application prospects. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The heat-resistant low-carbon concrete of the present invention comprises the following components in parts by weight: 300-350 parts of cement, 110-150 parts of composite admixture, 1000-1400 parts of refractory aggregate, 650-850 parts of granite powder sand, 50-60 parts of heat-shrinkable basalt fiber, 3.5-8.0 parts of water reducer, and 142-165 parts of water;

[0037] The preparation method of refractory aggregate comprises the following steps:

[0038] S1. The tuff powder and the NaOH solution are mixed evenly, and the modified tuff powder is obtained after drying;

[0039] S2. Add corncob ash, silicate cement and modified tuff powder into a granulator, stir evenly, spray water for granulation, and obtain aggregate with a particle size of 5 to 10 mm after sieving;

[0040] S3. The obtained aggregate is frozen at -10 to -5°C, and after low-temperature vacuum drying, it is cured at 20°C and 50% relative humidity for 20 to 24 hours. After the curing is completed, the aggregate is soaked in water for 12 to 24 hours to obtain an aggregate in a saturated surface dry state, which is a refractory aggregate.

[0041] As an optional embodiment, in step S1, the mass ratio of the tuff powder to the NaOH solution is (0.6-1.2): (6-10), and the mass concentration of the NaOH solution is 6%-12%. In step S2, the mass ratio of the corncob ash, silicate cement, modified tuff powder and water is (0.6-1.5): (2-6): (0.5-2.0): (0.7-2.5). In step S3, the low-temperature vacuum drying condition is sublimation drying at a temperature of -60--40°C and a vacuum of 10-30Pa for 20-24h.

[0042] As an optional embodiment, the method for preparing the heat-shrinkable basalt fiber comprises the following steps:

[0043] P1. The basalt fiber and spodumene are mixed and ground, kept at 150-250°C for 10-14h, then heated to 350-450°C for 10-14h, then heated to 550-650°C for 0.5-1.5h, and then cooled to obtain a mixed powder;

[0044] P2. The obtained mixed powder is evenly mixed with high-rubber powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2, and heat-shrinkable basalt fiber is obtained after melt extrusion, spinning and cutting.

[0045] As an optional embodiment, in step P1, the mass ratio of the basalt fiber to spodumene is (2-7): (4-10). In step P2, the mass ratio of the mixed powder to high-rubber powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2 is (8-15): (10-20): (8-15): (5-10): (2-5): (0.5-2.0). The compatibilizer is obtained by copolymerization of styrene and maleic anhydride.

[0046] The composite admixture comprises silica fume and fly ash in a mass ratio of 1: (1-2).

[0047] In the following embodiments and comparative examples, the average particle size of corncob ash is 100-200 μm, the SiO2 content is 66.38 wt%, the Al2O3 content is 7.48 wt%, the Fe2O3 content is 4.44 wt%, the CaO content is 11.57 wt%, and the MgO content is 2.06 wt%.

[0048] Example 1

[0049] This embodiment provides a heat-resistant low-carbon concrete, comprising the following components in parts by weight: 320 parts of high aluminate cement CA50-II, 50 parts of silica fume, 80 parts of fly ash, 1200 parts of refractory aggregate, 750 parts of granite silt sand, 60 parts of heat-shrinkable basalt fiber, 5.5 parts of polycarboxylate water-reducing agent, and 150 parts of water;

[0050] Wherein, the preparation method of refractory aggregate is as follows:

[0051] S1. The tuff powder and NaOH solution (10 wt%) were mixed in a mass ratio of 1:7.5, stirred for 10 min, and then placed in an oven at 80 ° C for drying to obtain modified tuff powder; the corn cob was placed in a muffle furnace, calcined at 815 ° C for 2 h, and cooled to room temperature to obtain corn cob ash;

[0052] S2. Add corncob ash, PO·42.5 silicate cement and modified tuff powder into a pan granulator in a mass ratio of 1:3:1.2, stir at 30 rpm and a slope of 40 degrees for 5 minutes, then spray water into the pan (the ratio of the mass of water to the total mass of corncob ash, cement and tuff powder is 0.25), stir at a speed of 55 rpm for 15 minutes to granulate the powder, and obtain aggregate with a particle size of 5 to 10 mm after sieving, and then store the water-saturated aggregate in a sealed plastic bag for later use.

[0053] S3. Freeze the obtained aggregate at -10°C for 12 hours, then sublimate and dry it at -45°C and vacuum 18Pa for 24 hours, then cure it at 20°C and 50% relative humidity for 24 hours. After curing, soak it in water for 24 hours to obtain aggregate in a saturated surface dry state, which is the refractory aggregate.

[0054] The preparation method of heat shrinkable basalt fiber is as follows:

[0055] P1. Put basalt fiber and spodumene in a ball mill at a mass ratio of 4:7 and grind for 6 hours, then heat to 200°C at a rate of 3°C / min and keep warm for 12 hours, then heat to 400°C at a rate of 3°C / min and keep warm for 12 hours, finally heat to 600°C at a rate of 3°C / min and keep warm for 1 hour, and then cool in the furnace to obtain a mixed powder;

[0056] P2. The obtained mixed powder is evenly mixed with high-glue powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2 in a mass ratio of 10:15:10:7.5:3:1, heated to 1600℃ for melt blending for 2h under argon protection, then extruded by a twin-screw extruder at a speed of 170rpm / min to obtain roving, and then connected to a wire drawing machine, the temperature in the wire drawing machine is controlled at 800℃, and the speed of the wire drawing machine is controlled at 300m / min to obtain filaments with a diameter of 10-20μm, and finally the filaments are cut into 12mm by a cutting machine to obtain heat-shrinkable basalt fibers.

[0057] This embodiment also provides a method for preparing heat-resistant low-carbon concrete, comprising the following steps:

[0058] M1. Weigh each component by weight;

[0059] M2. Mix high aluminate 42.5 cement, silica fume and fly ash for 1 minute, then add granite powder sand, polycarboxylic acid water reducer and water, stir for 2 minutes, add refractory aggregate, stir for 1 minute, add heat shrinkable basalt fiber through a sieve, and obtain heat-resistant low-carbon concrete after mixing.

[0060] Example 2

[0061] The heat-resistant low-carbon concrete of this embodiment is basically the same as that of Embodiment 1, except that the heat-resistant low-carbon concrete of this embodiment includes the following components in parts by weight: 300 parts of high aluminate cement CA50-II, 60 parts of silica fume, 90 parts of fly ash, 1300 parts of refractory aggregate, 650 parts of granite silt sand, 50 parts of heat-shrinkable basalt fiber, 8 parts of polycarboxylate water-reducing agent, and 142 parts of water;

[0062] Wherein, the preparation method of refractory aggregate is as follows:

[0063] S1. The tuff powder and NaOH solution (6 wt%) were mixed in a mass ratio of 0.6:10, stirred for 10 min, and then placed in an oven at 60 ° C for drying to obtain modified tuff powder; the corn cob was placed in a muffle furnace, calcined at 815 ° C for 2 h, and cooled to room temperature to obtain corn cob ash;

[0064] S2. Add corncob ash, PO·42.5 silicate cement and modified tuff powder into a pan granulator at a mass ratio of 1.5:2:2, stir at 30 rpm and a slope of 40 degrees for 10 min, then spray water into the pan (the ratio of the mass of water to the total mass of corncob ash, cement and tuff powder is 0.25), stir at 55 rpm for 10 min to granulate the powder, obtain aggregate with a particle size of 5 to 10 mm after sieving, and then store the water-saturated aggregate in a sealed plastic bag for later use.

[0065] S3. Freeze the obtained aggregate at -5°C for 12 hours, then sublimate and dry it at -45°C and vacuum 18Pa for 20 hours, and then cure it at 20°C and 50% relative humidity for 24 hours. After curing, soak it in water for 24 hours to obtain aggregate in a saturated surface dry state, which is the refractory aggregate.

[0066] The preparation method of heat shrinkable basalt fiber is as follows:

[0067] P1. Put basalt fiber and spodumene in a ball mill at a mass ratio of 2:4 and grind for 6 hours, then heat to 150°C at a rate of 3°C / min and keep it for 14 hours, then heat to 450°C at a rate of 3°C / min and keep it for 10 hours, finally heat to 650°C at a rate of 3°C / min and keep it for 0.5 hours, and then cool in the furnace to obtain a mixed powder;

[0068] P2. The obtained mixed powder is evenly mixed with high-rubber powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2 in a mass ratio of 8:10:15:5:2:0.5, heated to 1400℃ for melt blending for 3 hours under argon protection, and then extruded by a twin-screw extruder at a speed of 150rpm / min to obtain roving, and then connected to a wire drawing machine, the temperature in the wire drawing machine is controlled at 600℃, and the speed of the wire drawing machine is controlled at 200m / min to obtain filaments with a diameter of 10-20μm, and finally the filaments are cut into 12mm by a cutting machine to obtain heat-shrinkable basalt fibers.

[0069] Example 3

[0070] The heat-resistant low-carbon concrete of this embodiment is basically the same as that of Embodiment 1, except that the heat-resistant low-carbon concrete of this embodiment includes the following components in parts by weight: 350 parts of high aluminate cement CA50-II, 40 parts of silica fume, 70 parts of fly ash, 1000 parts of refractory aggregate, 850 parts of granite silt sand, 55 parts of heat-shrinkable basalt fiber, 4 parts of polycarboxylate water-reducing agent, and 165 parts of water;

[0071] Wherein, the preparation method of refractory aggregate is as follows:

[0072] S1. The tuff powder and NaOH solution (12 wt%) were mixed in a mass ratio of 1.2:6, stirred for 10 min, and then placed in an oven at 80° C. for drying to obtain modified tuff powder; the corn cob was placed in a muffle furnace, calcined at 850° C. for 2 h, and cooled to room temperature to obtain corn cob ash;

[0073] S2. Add corncob ash, PO·42.5 silicate cement and modified tuff powder into a pan granulator at a mass ratio of 0.6:6:0.5, stir at 30 rpm and a slope of 40 degrees for 5 minutes, then spray water into the pan (the ratio of the mass of water to the total mass of corncob ash, cement and tuff powder is 0.25), stir at a speed of 55 rpm for 15 minutes to granulate the powder, and obtain aggregate with a particle size of 5 to 10 mm after sieving, and then store the water-saturated aggregate in a sealed plastic bag for later use.

[0074] S3. Freeze the obtained aggregate at -10°C for 12 hours, then sublimate and dry it at -45°C and vacuum 18Pa for 24 hours, then cure it at 20°C and 50% relative humidity for 24 hours. After curing, soak it in water for 24 hours to obtain aggregate in a saturated surface dry state, which is the refractory aggregate.

[0075] The preparation method of heat shrinkable basalt fiber is as follows:

[0076] P1. Put basalt fiber and spodumene in a ball mill at a mass ratio of 7:10 and grind for 6 hours, then heat to 250℃ at a rate of 3℃ / min, keep warm for 10 hours, then heat to 350℃ at a rate of 3℃ / min, keep warm for 14 hours, and finally heat to 550℃ at a rate of 3℃ / min, keep warm for 1.5 hours, and cool in the furnace to obtain a mixed powder;

[0077] P2. The obtained mixed powder is evenly mixed with high-glue powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2 in a mass ratio of 15:20:8:10:5:2, heated to 1600℃ for melt blending for 2h under argon protection, then extruded by a twin-screw extruder at a speed of 170rpm / min to obtain roving, and then connected to a wire drawing machine, the temperature in the wire drawing machine is controlled at 800℃, and the speed of the wire drawing machine is controlled at 300m / min to obtain filaments with a diameter of 10-20μm, and finally the filaments are cut into 12mm by a cutting machine to obtain heat-shrinkable basalt fibers.

[0078] Comparative Example 1

[0079] The concrete of Comparative Example 1 is substantially the same as that of Example 1, except that basalt aggregate with a particle size of 5-10 mm is used instead of refractory aggregate in this comparative example.

[0080] Comparative Example 2

[0081] The concrete of Comparative Example 2 is substantially the same as that of Example 1, except that basalt fibers with a diameter of 10-20 μm and a length of 12 mm are used in this comparative example instead of heat-shrinkable basalt fibers.

[0082] Comparative Example 3

[0083] The concrete of Comparative Example 3 is substantially the same as that of Example 1, except that, in the method for preparing the refractory aggregate, the corn cob is placed in a muffle furnace, calcined at 600° C. for 2 h, and then cooled to room temperature to obtain corn cob ash.

[0084] Comparative Example 4

[0085] The concrete of Comparative Example 4 is substantially the same as that of Example 1, except that, in step S2, corncob ash is omitted and the amount of modified tuff powder is increased accordingly.

[0086] Comparative Example 5

[0087] The concrete of Comparative Example 5 is substantially the same as that of Example 1, except that, in step S2, the modified tuff powder is omitted and the amount of corncob ash is increased accordingly.

[0088] Comparative Example 6

[0089] The concrete of Comparative Example 6 is substantially the same as that of Example 1, except that, in step S3, the freeze-drying method is replaced by heating at 100° C. under normal atmospheric pressure.

[0090] Test example

[0091] The mixed concrete of the embodiment and the comparative example was made into 150mm×150mm×150mm cubic concrete test blocks. After one group of test blocks were demolded and cured for 28 days, the compressive strength and crack resistance of the concrete were tested. After another group of test blocks were demolded and cured for 28 days, they were placed in a 110°C oven for drying for 24 hours, and then placed in a high-temperature furnace and calcined at a constant temperature of 300°C and 600°C for 3 hours, respectively, and then naturally cooled to room temperature. The compressive strength and crack resistance of the concrete after calcination were tested. The test results are shown in Table 1.

[0092] The compressive strength of concrete is tested in accordance with the relevant provisions of GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Ordinary Concrete"; the crack resistance of concrete is tested in accordance with the relevant provisions of GB / T 50082-2009 "Standard for Test Methods for Long-term Properties and Durability of Ordinary Concrete".

[0093] Table 1 Compressive strength and crack resistance of concrete

[0094]

[0095] From the data in Table 1, it can be seen that the concretes of Examples 1 to 3 of the present invention have excellent mechanical strength and crack resistance. Even after high-temperature treatment, the concrete still has a high compressive strength and a low number of cracks per unit area, indicating that the concrete of the present invention has excellent heat resistance. This is because the refractory aggregate prepared by the present invention has a structure with a closed outer surface and a porous inner surface, which significantly reduces the thermal conductivity and thermal expansion coefficient of the concrete, and at the same time cooperates with the heat shrinkage effect of the heat-shrinkable basalt fiber to improve the heat resistance of the concrete.

[0096] By comparing Example 1 and Comparative Example 1, it can be found that compared with basalt aggregate, the refractory aggregate prepared by the present invention has the characteristics of a closed porous structure, which effectively reduces the heat transfer efficiency in concrete, and the thermal expansion deformation of the concrete is relatively reduced, further improving the crack resistance of the heat-resistant concrete at high temperatures.

[0097] By comparing Example 1 and Comparative Example 2, it can be found that, compared with basalt fiber, the use of heat-shrinkable basalt fiber can improve the mechanical strength and crack resistance of concrete at high temperatures; this is because at high temperatures, the heat-shrinkable basalt fiber uses its high-temperature shrinkage characteristics to generate pre-tension on aggregates and cementitious materials, resist the expansion stress inside the concrete, and prevent the internal deformation of the concrete from causing cracks.

[0098] Compared with Example 1, Comparative Example 3 uses corncob ash calcined at 600°C, and the thermal stability of concrete is seriously reduced. After the test block is calcined at 600°C, the compressive strength of the concrete decreases by 22.8%, which reduces the safety of heat-resistant concrete. Through scanning electron microscopy analysis of corncob ash, it is found that the surface of corncob ash calcined at 600°C is prone to adhesion, forming large flocculent particles, and there are obvious large particle slag blocks. Part of the corncob is not fully burned, and there is still a small amount of combustible components in the ash. The contents of SiO2, Al2O3, and Fe2O3 in the corncob ash are reduced.

[0099] Compared with Example 1, Comparative Example 4 lacks corn cob ash, the cement setting time is shortened, and the aggregate sets and hardens before being saturated with water during the hardening and molding process, which reduces the porosity of the refractory aggregate accordingly, increases the thermal expansion coefficient of the refractory aggregate, and has limited effect on improving the heat resistance of the concrete.

[0100] Compared with Example 1, Comparative Example 5 lacks modified tuff powder and increases the amount of corn cob ash. Since the activity of corn cob ash is lower than that of modified tuff powder, the coagulation and hardening strength of the refractory aggregate decreases, resulting in a 8.0% decrease in the 28-day concrete strength. At the same time, due to the lack of water absorption of tuff powder, the porosity of the refractory aggregate is reduced. Compared with Example 1, the number of concrete cracks increased by 6.6 cracks / m at a high temperature of 600°C. 2 .

[0101] Compared with Example 1, Comparative Example 6 does not adopt freeze-drying, and the obtained refractory aggregate does not contain a closed porous structure. The thermal expansion coefficient of the refractory aggregate increases, and the internal heat transfer coefficient of the concrete also increases accordingly. The mechanical properties and crack resistance of the concrete are significantly reduced due to thermal expansion.

[0102] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A heat-resistant low-carbon concrete, characterized in that: The invention comprises the following components in parts by weight: 300-350 parts of cement, 110-150 parts of composite admixture, 1000-1400 parts of refractory aggregate, 650-850 parts of granite silt sand, 50-60 parts of heat shrinkable basalt fiber, 3.5-8.0 parts of water reducing agent and 142-165 parts of water; The preparation method of the refractory aggregate comprises the following steps: S1. The tuff powder and the NaOH solution are mixed evenly, and the modified tuff powder is obtained after drying; S2. Add corncob ash, silicate cement and modified tuff powder into a granulator, stir evenly, spray water for granulation, and obtain aggregate with a particle size of 5 to 10 mm after sieving; S3. The obtained aggregate is frozen at -10 to -5°C and then subjected to low-temperature vacuum drying to obtain the refractory aggregate; The preparation method of the heat-shrinkable basalt fiber comprises the following steps: P1. The basalt fiber and spodumene are mixed and ground, kept at 150-250°C for 10-14h, then heated to 350-450°C for 10-14h, then heated to 550-650°C for 0.5-1.5h, and then cooled to obtain a mixed powder; P2. The obtained mixed powder is evenly mixed with high-rubber powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2, and heat-shrinkable basalt fiber is obtained after melt extrusion, spinning and cutting.

2. The heat-resistant low-carbon concrete according to claim 1, characterized in that: In step S1, the mass ratio of the tuff powder to the NaOH solution is (0.6-1.2):(6-10), and the mass concentration of the NaOH solution is 6%-12%.

3. The heat-resistant low-carbon concrete according to claim 1, characterized in that: In step S2, the mass ratio of corncob ash, silicate cement, modified tuff powder and water is (0.6-1.5): (2-6): (0.5-2.0): (0.7-2.5).

4. The heat-resistant low-carbon concrete according to claim 1, characterized in that: In step S3, the low-temperature vacuum drying is carried out under the conditions of sublimation drying at a temperature of -60 to -40°C and a vacuum of 10 to 30 Pa for 20 to 24 hours.

5. The heat-resistant low-carbon concrete according to claim 1, characterized in that: In step P1, the mass ratio of the basalt fiber to spodumene is (2-7):(4-10).

6. The heat-resistant low-carbon concrete according to claim 1, characterized in that: In step P2, the mass ratio of the mixed powder to high-rubber powder, nano-CaCO3 powder, compatibilizer, TiO2 and SnO2 is (8-15): (10-20): (8-15): (5-10): (2-5): (0.5-2.0).

7. The heat-resistant low-carbon concrete according to claim 1, characterized in that: The compatibilizer is obtained by copolymerizing styrene and maleic anhydride.

8. The heat-resistant low-carbon concrete according to claim 1, characterized in that: The composite admixture comprises silica fume and fly ash in a mass ratio of 1: (1-2).

9. The method for preparing heat-resistant low-carbon concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: M1. Weigh each component by weight; M2. The cement and composite admixture are mixed evenly, and then the granite silt sand, water reducer and water are added. After mixing evenly, the refractory aggregate is added. After mixing evenly, the heat-shrinkable basalt fiber is added. After mixing, pouring, curing and demolding, heat-resistant low-carbon concrete is obtained.

Citation Information

Patent Citations

  • Heat-resistant refractory concrete and preparation method thereof

    CN111908870A

  • Clinked tuff powder synergistically reinforced recycled aggregate, preparation method and cement stabilized macadam base

    CN115321863A